Presidential Vote Share and COVID-19 Vaccination Rate in Indonesia: A District-level Cross-Sectional Ecological Study - Wirawan, Gede Benny Setia; Gustina, Ni Luh Zallila; Valerie, Ivy Cerelia; Pradnyani RS, I Gusti Ayu Indah; Arifin, Muchamad Zaenal; Januraga, Pande Putu (Kesmas, 2023)
Political affiliation has been reported as a determinant of COVID-19 vaccine acceptance in some countries, although few studies have examined the Asian context. This study aims to fill this gap by employing an ecological study design using Indonesian regions as data points. Political affiliation was represented by incumbent President Jokowi’s vote share in the 2019 presidential election. Potential confounders included population density, human development index, availability of hospitals and primary health care, 2019–2020 economic growth, COVID-19 mortality rate, and proportion of Muslims in the population. The final analysis included 201 out of 501 districts and cities in Indonesia. Controlling for confounders, multivariate regression found that Jokowi’s vote share was an independent predictor of vaccination rate, with standardized β and R2 values of 0.350 and 0.734 for the first dose vaccination rates and 0.251 and 0.782 for the second dose, respectively. This association may be underpinned by differences in religiosity, public trust, and vulnerability to misinformation between Jokowi’s supporters and the opposition. Improving public trust in a politically polarizing society is crucial to improving future coverage of COVID-19 and other vaccines.